Mechanistic studies of first-row transition metal catalyzed homogeneous CO2 reduction via H2 using density functional theory - Yao, Linbin (2021)
CO2 reduction has been quite a hot research topic, and its catalytic reduction mechanisms via H2 using homogeneous transition metal based catalysts, especially first-row transition metal (Cu and Mn) complex catalysts, haven’t been thoroughly studied yet. In this thesis, mechanistic studies using density functional theory (DFT) have been conducted to understand the reaction mechanisms and possible factors (e.g. basicity of added reagent) at the molecular level, which will fill the research gap in this area and provide insights for rational catalyst design. To sum up, the thesis contains two chapters to first introduce the research background and methodology (Chapter 1 and 2), two main chapters to present the DFT studies of Cu and Mn based systems (Chapter 3 and 4), and one extra chapter to demonstrate how the DFT studied have been expanded to other homogeneous catalytic systems (Chapter 5).